Tekstilna zbirka Slovenskega etnografskega muzeja - Žagar, Janja (Etnolog. Nova vrsta (Ljubljana), 2003)
The article presents the textile collection of the Slovene Ethnographic Museum: what formed the collection, what is it today and what it is not. How is it structured and how is internally and externally valued. Reflecting on the criteria for collecting objects from the industrial and consumer societies and on the themes which will set the framework for theoretical study, the article suggests guidelines for the expansion, formation and interpretation of the collection in the future.
Keywords: Slovenski etnografski muzej; Ljubljana; cultural heritage; kulturna dediščina; oblačilna kultura